The human hypothalamus in mood disorders: The HPA axis in the center. (June 2019) - Bao, Ai-Min; Swaab, Dick F.
Abstract: There are no specific structural neuropathological hallmarks found in the brain of mood disorders. Instead, there are molecular, functional and structural alterations reported in many brain areas. The neurodevelopmental underpinning indicated the presence of various genetic and developmental risk factors. The effect of genetic polymorphisms and developmental sequalae, some of which may start in the womb, result in functional changes in a network mediated by neurotransmitters and neuropeptides, which make the emotion- and stress-related brain systems more vulnerable to stressful events. This network of stress-related neurocircuits consists of, for instance, brainstem nuclei, the amygdala, habenula, prefrontal cortex and hypothalamus. Various nuclei of the hypothalamus form indeed one of the crucial hubs in this network. This structure concerns not only the hypothalamo-pituitary-adrenal (HPA) axis that integrate the neuro-endocrine-immune responses to stress, but also other hypothalamic nuclei and systems that play a key role in the symptoms of depression, such as disordered day-night rhythm, lack of reward feelings, disturbed eating, sex, and disturbed cognitive functions. The present review will focus on the changes in the human hypothalamus in depression, with the HPA axis in the center. We will discuss the inordinate network of neurotransmitters and neuropeptides involved, with the hope to find the most vulnerable neurobiological systems and the possible development of tailor-made treatments for mood disorders in the future.